Características físicas e morfológicas do sêmen de Bos taurus e Bos indicus antes e após a criopreservação - Franciscato, Douglas Augusto [UNESP] (2015)
This study aimed to verify the changes that occur in sperm cells during the process of cryopreservation between the different subspecies Bos taurus and Bos indicus. Semen from 20 animals (10 of each subspecies) fresh and after cryopreservation / thawing, were analyzed for motility, sperm morphology, plasma membrane and acrosome integrity, lipid peroxidation, chromatin condensation and sperm head morphology. The fresh semen evaluations results of the subspecies Bos taurus showed higher motility when compared to Zebu (68.00% ± 6.32% and 63.00% ± 4.83% respectively). European animals showed better freezability semen, in general, because their sperm were less affected by the cryopreservation process (B. taurus - Motility (%): 38.00 ± 7.88, HYPO (%): 40.4 ± 6.45, Area : 11556.14 ± 2055.46, Perimeter: 25.17 ± 1.87, Width: 5.22 ± 0.96, Fourier 2: 7867.27 ± 1965.47;1 B. indicus - Motility: 30.00 ± 4.71, HYPO: 27.5 ± 6.98, area: 12416.06 ± 2232.06, Perimeter: 26.02 ± 2.02, Width: 5.31 ± 0.97, Fourier 2: 8536.77 ± 2058.21). It was observed that cryopreservation damages all sperm structures, regardless of subspecies, indicating that improvements in this technique are still needed